2021
DOI: 10.3390/ijerph182212068
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of PhD Students at Polish Universities—Before the COVID-19 Outbreak

Abstract: Background: A group particularly exposed to the occurrence of disorders in the sphere of the psyche are young people with a newly developing personality structure and a sense of identity. In the available literature there are few reports describing the mental health of doctoral students—a group that is affected by a particular group of stressors. The aim of the research was to assess the mental health of PhD students at Polish universities. Material and Methods: The Polish adaptation of the GHQ Questionnaire-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Among Czech students, first-degree students were less likely to have anxiety and depression and second-degree students were less likely to have anxiety compared to third-degree students. These findings indicate that doctoral students can be considered a risk group (31). The truth is that the degree of study should not be underestimated when examining students' mental health.…”
Section: Study Specificsmentioning
confidence: 76%
See 1 more Smart Citation
“…Among Czech students, first-degree students were less likely to have anxiety and depression and second-degree students were less likely to have anxiety compared to third-degree students. These findings indicate that doctoral students can be considered a risk group (31). The truth is that the degree of study should not be underestimated when examining students' mental health.…”
Section: Study Specificsmentioning
confidence: 76%
“…In other words, students' anxiety has a negative effect on their academic motivation ( 29 ). It is also possible to point out the somatic complaints that can occur in college students, not only during the COVID-19 pandemic ( 30 , 31 ). Somatic complaints are serious concomitant symptoms of poor mental health and should not be overlooked in research.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it can be concluded that the degree of study is a factor that needs increased attention, especially in terms of anxiety. In view of the results, there is a need to monitor third-degree students, as emphasized by Kowalczyk et al ( 37 ). Other studies have also shown that the study degree is an important factor in examining mental health problems among students ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following the above-mentioned facts, college students around the world often suffered from stress, depression, and anxiety during the COVID-19 pandemic, as evidenced by the high prevalence rates found in various studies ( 13 , 15 , 18 , 34 36 ). These problems vary from student to student, but it is well-known that study-related characteristics such as degree of study ( 37 39 ), form of study ( 39 , 40 ), field of study ( 3 , 41 – 43 ), and distance from home and family while studying ( 44 47 ) play an important role. Evidence shows that all of the mentioned mental health problems are positively associated with inadequate-self and hated-self among college students ( 48 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results are quite interesting given the importance that mental health is currently gaining as it has been highlighted by several research studies in different countries around the world [5][6] . Linked to this, these observations have become more relevant and evident after the significant impact of the COVID-19 pandemic on the mental health of doctoral students [7][8][9] .…”
Section: Summary Of Survey Results During the Meet And Greet Eventmentioning
confidence: 94%